Empati: Jalan Mengurangi Konflik pada Pemilihan Umum Presiden dan Wakil Presiden 2024 - Faiz Yunsar Hammam; Rakhmaditya Dewi Noorizki (Universitas Negeri Malang, 2024)
Indonesia is a country based on the democracy of Pancasila. Elections are one of the important pillars in the world of politics in a democratic country. Election, especially the election of president and vice president, gives the right to all Indonesian citizens who already have the right to vote, both within the country and abroad, to choose suitable candidate pairs to lead Indonesia in the future. The large voting population allows for a variety of voters for each existing candidate, and it is not uncommon for conflicts to arise from partiality towards one of the presidential and vice presidential candidate pairs. Such a conflict is based on a lack of empathy between the two supporters of the two presidential and vice presidential candidates. By writing this article, the researcher wants to describe how empathy can minimize or even prevent societal conflict with differences in the interests of the 2024 presidential and vice presidential candidates. This article was prepared using descriptive qualitative methods. The result shows that empathy can reduce the possibility of conflict in the 2024 presidential and vice presidential general elections, which are viewed from 4 aspects of empathy, namely the affective dimension, moral dimension, cognitive dimension, and behavioral dimension. AbstrakIndonesia adalah negara yang berdasarkan demokrasi pancasila. Pemilu menjadi salah satu pilar penting di dunia politik dalam negara demokrasi. Pemilu, khususnya pada pemilihan presiden dan wakil presiden, memberikan hak kepada suluruh warga Negara Indonesia yang sudah memiliki hak pilih, baik yang di dalam negeri maupun di luar negeri untuk memilih pasangan calon yang pantas untuk memimpin Indonesia kedepannya. Banyaknya populasi pemilih memungkinkan beragamnya pemilih untuk setiap calon yang ada dan tidak jarang akan timbul konflik dari adanya keberpihakan kepada salah satu pasangan calon presiden dan wakil presiden. Konflik seperti itu didasari atas kurangnya empati antar kedua pendukung kedua calon presiden dan wakil presiden tersebut. Dengan penulisan artikel ini peneliti ingin mengetahui gambaran empati dalam meminimalisir atau bahkan mencegah konflik masyarakat dengan perbedaan minat pasangan calon presiden dan wakil presiden 2024. Artikel ini disusun dengan menggunakan metode kualitatif deskriptif. Hasil penelitian yang dilakukan menunjukkan empati dapat mengurangi kemungkinan adanya konflik di pemilihan umum presiden dan wakil presiden 2024 yang ditinjau dari 4 aspek empati yaitu dimensi afektif, dimensi moral, dimensi kognitif, dan dimensi perilaku.